Study on myopathy, neuropathy in STZ-induced Diabetes mellitus experimental rats Rattus norvegicus and the role of arginine in prevention of complications - Mohammed k. Hassani; Maha K. Ibrahim ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2019)
The study was designed to clarified the effect of induced diabetes mellitus (DM) on myopathy , neuropathy in addition to the possible role of arginine in prevention of (DM) complications at each period (15,30,45) days post induction . Findings on non-sectioning method (silver nitrate) impregnation indicated that the isolated muscle fibers from skeletal muscle (Biceps - Triceps-Gastrocnemius) showed mild degeneration, increased myonuclei , areas of necrosis , reduced axons diameter, the motor-end plates endings retracted , undifferentiated nuclei at sole plate with dense sarcolemma at the neuromuscular junction , through the ( 30) days the changes more severity , results indicated to muscle fibers degeneration , most vesicular myonuclei appeared pyknotic , demyelination nerve fibers , atrophied axons , remnants of nerve fibers , tortous and the sarcolemma showed discontinuity , whereas isolated muscle fibers from diabetes muscles at (45) days revealed to sever reduction in muscle fiber diameter , some with cross striations , others have no Z-line , segmental demyelination , the motor endings lost their connection with their original nerve fibers and ends with retracted nerve endings compared to isolated muscle fibers from skeletal muscles impregnated with silver nitrate related to diabetes rats treated with arginine clarified that more regular muscle fibers , supplied with myelinated fibers , new formation of motor - end plate , the muscle fibers with cross striations , new myotubes , primary and secondary terminal branches end with developed nerve endings , these endings have variable shape, like cone , twigs , configurations at ( 15, 30) days post treated , the isolated muscle fibers from rats treated with arginine at ( 45 ) days post treated showed more myelinated fibers with constrictions , and variable endings , simple , secondary and grape like .